Deer antler reserve mesenchyme cells modified with miR-145 promote chondrogenesis in cartilage regeneration - Jia, Boyin; Han, Xintong; Li, Xin; Zhang, Linlin; Ma, Fuquan; Wang, Yusu; Wang, Xue; Yan, Yaru; Li, Yaxin; Shen, Junnan; Chen, Xinran; Li, Xinyi; et al. (Frontiers in Veterinary Science, 2024)
Deer antler-derived reserve mesenchyme cells (RMCs) are a promising source of cells for cartilage regeneration therapy due to their chondrogenic differentiation potential. However, the regulatory mechanism has not yet been elucidated. In this study, we analyzed the role of microRNAs (miRNAs) in regulating the differentiation of RMCs and in the post-transcriptional regulation of chondrogenesis and hypertrophic differentiation at the molecular and histological levels. The results showed that RMCs showed typical MSC differentiation potentials. During chondrogenic differentiation, we obtained the expression profile of miRNAs, among which miR- 145 was the most prominent candidate as a key microRNA involved in the balance of chondral and endochondral differentiation. Knockdown of miR-145 promoted chondrogenesis and inhibited hypertrophy differentiation in RMCs. Mechanically, by prediction through online databases combined with dual-luciferase reporter assay, SOX9 was suggested as a target of miR-145. Further validation experiments confirmed that knockdown of miR-145 contributed to the balance between endochondral versus chondral differentiation of RMCs by targeting SOX9. Additionally, RMCs transfected with the miR-145-knockdown-mediated lentiviral vector successfully promoted cartilage regeneration in vivo. In summary, our study suggested that the reciprocal negative feedback between SOX9 and miR-145 was essential for balancing between endochondral versus chondral differentiation of RMCs. Our study suggested that modification of RMCs using miRNAs transduction might be an effective treatment for cartilage defects.